2018
DOI: 10.1111/jsr.12730
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance in DSWPD patients upon awakening from habitual sleep compared with forced conventional sleep

Abstract: Difficult early morning awakening is one of the defining symptoms of delayed sleep-wake phase disorder. It is accompanied by low cognitive arousal and drowsiness resulting in difficulty concentrating and focusing attention upon awakening. We designed the current study to quantitate cognitive performance (i.e. omissions, commissions, reaction time [average and variability]) and cognitive domains (i.e. focused attention, sustained attention, impulsivity and vigilance) with Conners' Continuous Performance Test II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, whereas the controls performed better (faster with fewer lapses) in the morning, the DSWPD group performed poorer. The fact that the morning RTT was administered several hours after awakening (rise time at 07:00 h, testing at 10:00 h), suggests that the poor morning performance in the participants with DSWPD was not merely a transient effect of sleep inertia as has been suggested by Solheim et al (2018). These performance decrements are thus likely to be present throughout a school or workday of individuals with DSWPD, significantly affecting their daytime functioning.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, whereas the controls performed better (faster with fewer lapses) in the morning, the DSWPD group performed poorer. The fact that the morning RTT was administered several hours after awakening (rise time at 07:00 h, testing at 10:00 h), suggests that the poor morning performance in the participants with DSWPD was not merely a transient effect of sleep inertia as has been suggested by Solheim et al (2018). These performance decrements are thus likely to be present throughout a school or workday of individuals with DSWPD, significantly affecting their daytime functioning.…”
Section: Discussionmentioning
confidence: 86%
“…Few studies have investigated such time of day variations in performance in individuals with DSWPD by objectively measuring performance at different times of day in experimental, controlled settings. In a recent study, Solheim et al (2018) showed impaired morning performance on a sustained reaction time task in individuals with DSWPD, particularly following forced awakenings. However, since the participants in that study were tested immediately after awakening, the authors attributed the findings to sleep inertia, a transient period of confusion and reduced alertness following forced awakenings (Tassi and Muzet, 2000), rather than to the synchrony effect or effects of sleep curtailment.…”
Section: Introductionmentioning
confidence: 95%
“…34 Sleep restriction and higher circadian sleep propensity amplify the effects of sleep inertia on vigilance levels, 35 and both late chronotypes and DSWPD patients may present greater sleep inertia after forced awakenings compared to individuals with an earlier sleep schedule. 16,36 Subjective sleep quality was lower for the nights with mandatory WT in the two groups, which is interesting considering that sleep efficiency measured with actigraphy was identical in the two night conditions. Differences between objective and subjective evaluation of sleep quality have also been observed in previous studies on E-types and DSWPD patients.…”
Section: Discussionmentioning
confidence: 72%
“…Although the reason for this inconsistency among the studies was unclear, the composite score of the BACS-J might be representative of cognitive dysfunction in patients with MDD. Because few studies have shown a relationship between a delayed sleep-wake phase and cognitive dysfunction ( 7 ), it is difficult to interpret this result. One possible explanation for this relationship was that the delayed sleep-wake phase, which usually caused physical and mental dysfunction, daytime sleepiness, and loss of concentration, might deteriorate daytime cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Insomnia and circadian rhythm dysfunction, especially delayed sleep-wake rhythm, were commonly observed in patients with MDD ( 6 ). Recent studies have suggested that the delayed sleep-wake phase is likely to worsen depressive symptoms and cognitive dysfunctions ( 7 ). However, few studies have assessed influences of the delayed sleep-wake phase on depressive symptoms and functional impairment in patients with MDD.…”
Section: Introductionmentioning
confidence: 99%